Next-generation DNA sequencing of Panax samples revealed new genotypes: Burrows-Wheeler Aligner, Python-based abundance and clustering analysis - Christopher Oberc; Paul C.H. Li (Heliyon, 2024)
Background: There are two major species of the Panax genus, namely Panax ginseng and Panax quinquefolius. Other than the nucleic acid test and nucleic acid amplification test, DNA sequencing can be used to authenticate the species of ginseng samples, especially when their physical forms cannot be used for differentiation. Method: In this work, next generation sequencing was used to obtain millions of reads from fourteen ginseng samples (root, powder, and granule). Then Gaussian Mixture clustering analysis was applied to analyze the reads from each sample. Results and Discussion: A new genotype has been revealed in this study. Two samples have been authenticated with certainty, while the others may be hybrid in nature as revealed by the clustering results.